2009
DOI: 10.1080/10926770903307914
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Juveniles Who Sexually Offend in a Southwestern State

Abstract: A 25-item questionnaire was mailed to sex offender treatment providers from counties with 60 or more reported juvenile sex offenders in a Southwestern state to determine the most effective treatment for juvenile sex offenders. Results indicated that cognitive behavioral therapy was the most successful reported approach to treatment with an average success rate of 87%. The most commonly used approach was cognitive behavioral therapy with relapse prevention. The most common sexual offense was indecency with a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Providers report CBT is the most frequently used approach and is perceived by providers as the most effective (Ikomi, Harris-Wyatt, Geraldin, & Rodney, 2009). A meta-analysis evaluating various treatment approaches supports this perception, finding cognitive behavioral interventions to be consistently linked to self-reported low recidivism and low deviant sexual arousal and have the largest effect sizes .…”
Section: Current Treatment Approaches For Sexually Abusive Youthsmentioning
confidence: 69%
See 2 more Smart Citations
“…Providers report CBT is the most frequently used approach and is perceived by providers as the most effective (Ikomi, Harris-Wyatt, Geraldin, & Rodney, 2009). A meta-analysis evaluating various treatment approaches supports this perception, finding cognitive behavioral interventions to be consistently linked to self-reported low recidivism and low deviant sexual arousal and have the largest effect sizes .…”
Section: Current Treatment Approaches For Sexually Abusive Youthsmentioning
confidence: 69%
“…Some professionals advocate for both CBT and relapse prevention approaches as promising methods of service delivery (Guarino-Ghezzi & Kimball, 1998;Ikomi et al, 2009;Reitzel & Carbonell, 2006), while others are speculative and question the lack of rigor in the evaluations (Borduin & Schaeffer, 2001;Letourneau & Borduin, 2008). Extant research prevents making definitive claims that cognitive behavioral and relapse prevention interventions are evidencedbased.…”
Section: Current Treatment Approaches For Sexually Abusive Youthsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study, it has been reported that the same treatment is the most effective therapy for male adolescent sex offenders [36].…”
Section: Treatment Of the Juvenile Sex Offendermentioning
confidence: 99%
“…Worling suggested that adolescent sexual offenders need competency in social skills, like "interpreting verbal and nonverbal cues, regulating affect, gauging intention, active listening, and encouraging reciprocity." Social skills training is based on the assumption that social skills are critical to sexual offense risk reduction since the adolescent will require the skills and confidence to form future healthy intimate relationships [35,36].…”
Section: Treatment Of the Juvenile Sex Offendermentioning
confidence: 99%